(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the growth of forage cactus (Nopalea cochenillifera clone Doce Gigante), using different cladode fractionation methods. The experimental design used was completely randomized with five treatments, and each treatment was formed by 15 repetitions. In the control treatment the cladode was planted whole by the conventional method, in the second and third treatment the cladodes were divided in half (½) in a horizontal and vertical direction, respectively. In the fourth treatment the seedlings were composed of a fourth (¼) of the cladode and for the fifth treatment the segments were constituted with dimensions of 6.0 cm in height and 4.0 cm in width. During the experiment, the number of cladodes per plant, length, width and thickness of the cladodes were evaluated, using a digital caliper and metric measuring tape. The statistical analysis was performed with the R-project 2.13.1 software. In relation to the length, width and thickness of the cladode, a significant effect was observed between the treatments, so that the cladodes originated from the treatments with half (½) cladode with vertical cut were superior to the other treatments. It was observed that the plants that originated from the entire cladode had higher weight per plant. The multiplication technique by means of segments obtained from the cladode presents itself as a viable alternative for animal production systems in the Brazilian Semiarid, for the cultivation of forage cactus clone Doce Gigante. Cladodes cut in half vertically can be used for planting forage cactus clone Doce Gigante.